2022
DOI: 10.1186/s43141-022-00311-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide in silico identification of phospholipase D (PLD) gene family from Corchorus capsularis and Corchorus olitorius: reveals their responses to plant stress

Abstract: Background Plant grows in nature facing various types of abiotic stresses for their normal growth and development. During abiotic stress, plants evolve different types of mechanisms to survive in a hostile environment. Phospholipase D (PLD) plays important role in the regulation of diverse cellular processes including stress responses in plants. Member of PLD genes are well studied in different model plants; however, their functions in the jute are not clear yet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…capsularis and C . olitorius , respectively [ 56 ] 3 Identification of candidate genes regulating drought tolerance in pearl millet 74 drought-responsive genes separated into five phylogenic groups [ 57 ] 4 In-Silico study of Brassinosteroid (BR) signaling genes in rice 39 BR signaling genes [ 58 ] 5 Genome-wide in silico identification and characterization of sodium-proton (Na + /H +) antiporters in Indica rice sixteen NHX orthologous [ 59 ] 6 In silico identification and annotation of drought responsive candidate genes in Solanaceous 109 drought responsive unigenes [ 60 ] 7 In silico identification of Rare Cold Inducible 2 (RCI2) gene family in cucumber Four RCI2 genes 8 In silico identification and expression analysis of nuclear factor Y (Nf-Y) in cucumber 27 CsaNF-Y members [ 61 ] 9 Genome-wide In silico identification and comparative analysis of Dof gene family in Brassica napus 117 Brassica napus Dof genes ( BnaDofs ) [ 62 ] 10 Genome-wide identification and in silico analysis of nitrate transporters in hexaploid wheat 412 nitrate transporter genes [ 63 ] 11 VOZS identification from tef [ Eragrostis tef (Zucc.) Trotter] using in silico tools Four VOZs from tef …”
Section: Introductionmentioning
confidence: 99%
“…capsularis and C . olitorius , respectively [ 56 ] 3 Identification of candidate genes regulating drought tolerance in pearl millet 74 drought-responsive genes separated into five phylogenic groups [ 57 ] 4 In-Silico study of Brassinosteroid (BR) signaling genes in rice 39 BR signaling genes [ 58 ] 5 Genome-wide in silico identification and characterization of sodium-proton (Na + /H +) antiporters in Indica rice sixteen NHX orthologous [ 59 ] 6 In silico identification and annotation of drought responsive candidate genes in Solanaceous 109 drought responsive unigenes [ 60 ] 7 In silico identification of Rare Cold Inducible 2 (RCI2) gene family in cucumber Four RCI2 genes 8 In silico identification and expression analysis of nuclear factor Y (Nf-Y) in cucumber 27 CsaNF-Y members [ 61 ] 9 Genome-wide In silico identification and comparative analysis of Dof gene family in Brassica napus 117 Brassica napus Dof genes ( BnaDofs ) [ 62 ] 10 Genome-wide identification and in silico analysis of nitrate transporters in hexaploid wheat 412 nitrate transporter genes [ 63 ] 11 VOZS identification from tef [ Eragrostis tef (Zucc.) Trotter] using in silico tools Four VOZs from tef …”
Section: Introductionmentioning
confidence: 99%
“…Plants exploit lipid signaling to regulate a variety of cellular processes in response to external stimuli [1]. In this regard, phospholipids, which are the main components of biological membranes, can act as intracellular signaling molecules [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…They also found that most of the PLD gene family members in grape (10 out of 11) and poplar (13 out of 17) showed closer phylogenetically relationship together than with rice and Arabidopsis PLD gene members. Genome-wide in silico analysis of PLD genes from Corchorus olitorius and C. capsularis resulted in the identification of 20 different motifs where β1 and γ1, and all members of δ1 classes in both Corchorus species, represented the highest number of motifs [1]. Tissue-specific analysis of δ2, α2, and β1 subclasses revealed their roles involved in drought and salinity stresses.…”
Section: Introductionmentioning
confidence: 99%